Are patients knowledgeable about regulations concerning their obligations while undergoing treatment in the national health services institutions? - Wroński, Konrad; Bocian, Roman; Depta, Adam (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Background : Patients, while staying in hospital, are protected by patients’ rights. The National Health Services Institutions Act imposes an obligation on the NHS institutions to issue regulations in which patients’ duties will be listed. Aim: The aim of this research was to evaluate the patients’ knowledge about the existence of patients’ obligations and the necessity to comply with these during their stay in the NHS institutions. Material and methods : A group of 1500 patients treated in the Doctor Pirogow’s Specialized Hospital in Lodz was interviewed by means of the author’s own survey in which tools were used to examine patients’ knowledge about the presence of the patients’ obligations. The necessary statistics were conducted by means of STATISTICA 7.1 and EXCEL 2008 programmes. Results: The analysis of the results shows that 1140 (76.0%) respondents had no idea about the presence of obligations regulating appropriate behaviour during hospitalization. Among the 1500 respondents, 165 (11.0%) of them were knowledgeable about these rights. Conclusions : The results of this research demonstrate that patients are not knowledgeable about their obligations regula-ting appropriate behaviour during hospitalization. It should be a responsibility of medical staff to inform patients about the fact that patients’ obligations exist and also about the necessity to comply with these.